Governance in the metropolitan area of Valencia (Spain): an unfinished business - Zornoza-Gallego, Carmen; Pitarch-Garrido, Maria Dolores; Romero-González, Juan (Frontiers in Political Science, 2023)
Metropolitan government is still an unfinished business in Spain. An example of this is the metropolitan area of Valencia. The aim of this article is to learn about the process that has led to the current situation of a lack of metropolitan government and to propose actions that will help to make it a reality in the not-too-distant future. To this end, it analyses the history and the current regulations, and it is completed with the opinions and contributions of academics and politicians. The result is that, although there is no political will to include the consolidation of a metropolitan government in Valencia in the current political agenda, it is possible to set in motion initiatives of different types, on the part of local administrations and civil society, which can take advantage of the existing governance structures to advance toward a metropolitan government in the medium term.